Interaction of actin with plasminogen/plasmin system: mechanisms and physiological role - Tykhomyrov, A.A. (Вiopolymers and Cell, 2012)
In the present review, we have summarized and analyzed the literature data concerning cooperation between multifunctional proteins, the components of plasminogen/plasmin system and actin. The mechanisms underlying intermolecular interactions and the role of plasminogen kringle domains in protein-protein recognition are reviewed. A particular attention is paid to extracellular actin that serves as a surface protein of plasma membrane in various cells. A putative role of surface actin as the universal «non-hemostatic» center of plasminogen activation is discussed. The exposition of cytoskeletal actin on the outer surface of cellular membrane is thought to be a phenomenon, which is involved in both normal cell functioning and development of pathologies. In particular, the mechanism of plasminogen fragmentation on the surface of cancer cells mediated by actin, which results in generation of endogenous suppressors of tumor growth and metastazing (angiostatins), is described. It has been acknowledged that the plasminogen/plasmin system in concert with surface actin regulates releasing biologically active substances, e. g. catecholamines. The comprehensive assessment of plasminogen/plasmin system and surface actin exposition is proposed to be a criterion of functional status of cells and can be used as a diagnostic parameter at various pathologies. Keywords: multifunctional proteins, plasminogen/plasmin system, actin.